Reconception of Local Working Patent as a Form of Legal Progressivity in the Era of Disruption - Abel Parvez; Hafsah Aryandini; Gilang Rizki Aji Putra (Veteran Law Review, 2022)
Technological knowledge in the era of disruption has an important role in responding to the complex needs of society. In order to fulfill the needs, humans continue to produce new discoveries that need legal recognition and protection for the results of human intellectual abilities. One of the manifestations of intellectual wealth is in the form of patents. The main goal to be achieved is to encourage the creation, inventions and intellectual works of Indonesian citizens which in turn are able to create national independence. As an effort to control technology through patent rights, a Local Working Patent concept was formed which is regulated in Article 20 of Act Number 13 of 2016 on Patents. The Local Working Patent mandated in this article is in the form of a provision whereby when a patent has been granted by the state, the patent inventor is obliged to apply the patent in Indonesia to support technology transfer, investment and employment absorption. However, Act Number 11 of 2020 on Ciptaker eliminates this concept because this obligation is considered burdensome and can reduce investment from abroad. In this case the law should follow and oversee the needs and interests of the society. This means that the law must be progressive and must not be left behind by changes in society so that it can accommodate new existing interests. Based on this postulate, the writer wants to contribute in the form of a paper that comprehensively discusses the problems that exist in patent protection. The research method used is normative juridical research with a statutory approach and a conceptual approach. Thus, the author offers an idea in the form of a reconception of Local Working Patent which is ideal to be applied in Indonesia by meeting and fulfill the national and outsiders interests.